[18F]FDG PET/CT imaging for evaluating associations between glycolytic activity of brown adipose tissue, breast cancer progression and cachexia in a xenograft model - Ketonen, Petra (My University, 2023)
BACKGROUND Brown adipose tissue (BAT) is a thermogenetic organ that helps to regulate body temperature. Besides the normal biological function of BAT, a relationship between BAT activity, cancer progression and cachexia has been hypothesised to exist. The glycolytic activity of BAT and tumours can be detected by the use of fluorine-18 labelled 2-deoxy-2-[18F]fluoro-D-glucose ([18F]FDG; T1/2=109.8 min) positron emission tomography-computed tomography (PET/CT) imaging. OBJECTIVE This study aims to examine associations between glycolytic activity of BAT, breast cancer progression and cachexia in a xenograft model by utilising [18F]FDG PET/CT imaging after BAT-activation (beta-3-agonist; mirabegron) or BAT-inactivation (nonselective beta-blocker; propranolol). MATERIALS AND METHODS Female Athymic Nude-Foxn1nu mice (n = 40) were stratified into four groups (n = 10/per group): 1) control (no tumours, no medication), 2) sham (tumours, sham medication), 3) propranolol (tumours, propranolol 5 mg/kg), and 4) mirabegron (tumours, mirabegron 5 mg/kg). MDA-MB-231 breast cancer cells were subcutaneously inoculated one week after the beginning of treatment (orally, 5/week, 33 days). The glycolytic activity of BAT and tumours were monitored using baseline and follow-up [18F]FDG PET/CT scans. The glycolytic activity was determined as mean standardised uptake value (SUVmean), metabolic volume (BMV) and total metabolic activity (TMA) for BAT, or metabolic tumour volume (MTV) and total glycolytic lesion (TLG) for tumour. Tumour growth and body composition (body weight, lean and fat mass) were monitored weekly. RESULTS Baseline scan showed no significant differences in glycolytic activity of BAT between the groups. In the follow-up scan, mirabegron group showed significantly lower glycolytic activity, as measured by SUVmean, in BAT compared to the control group. Tumour incidence differed significantly between the groups, showing a median latency of 9, 12.5 and 19.5 days for mirabegron, sham and propranolol groups, respectively. However, tumour growth kinetics was similar in all groups. All groups showed an increase in body weight, lean and fat mass over time without any signs of cachexia in tumour-bearing mice. CONCLUSIONS Long-term administration of propranolol and mirabegron did not display the expected inactivation or activation of glycolytic activity in BAT. Unexpectedly, mirabegron-treated mice showed the lowest glycolytic activity, as measured by SUVmean, at the study endpoint. Even so, mirabegron treatment seems to accelerate, while propranolol treatment slows down the tumour incidence without influencing the tumour growth kinetics. This study was not able to show an association between glycolytic activity of BAT, cancer progression and cachexia in this xenograft model.
Keywords: Keywords: Brown adipose tissue (BAT), breast cancer, cachexia, [18F]FDG PET/CT